Pemikiran Mohammad Mahfud MD tentang Politik Hukum Islam di Indonesia - Itmam, Muhammad Shohibul; syakirin, ahmad (State Islamic Institute of Kudus (IAIN Kudus), 2019)
This paper explains the problem of the journey of Islamic law towards positive law in Indonesia in the perspective of legal politics Mahfud MD with the aim of actualizing Islamic law in the present in the Indonesian context. With a normative legal approach, analytical descriptive, this paper concludes that the actualization of Islamic legal politics in the thinking of Mahfud MD can be done through two approaches. The first is the cultural approach that massively Islamic law directly interacts with the culture and traditions that apply and develop in certain societies. Through acculturation of culture, Islamic law can adjust adaptation and dialogue with various social societies with a variety of traditions dynamically without losing theirauthenticity as humanitarian teachings. Both substantive approaches prioritize the spirit of Islamic universalism by not formalizing Islamic law positively both in law, local regulations and so on. Thus the actualization of Islamic law politics Mahfud MD is an offer to the formulation of Islamic law with the positivation of Islamic law in Indonesia through an elaborative approach combining cultural approaches and substantive approaches to real Indonesian law. Keywords: Actualization, Islamic Law, Political Law, Mahfud MD